Penerapan Collaborative Knowledge Creation dan Pentahelix dalam Meningkatkan Daya Saing UMKM di Depok dan DKI Jakarta - Mariam, Iis; Wartiningsih , Endah; Purwinarti , Titik; Eko Putro , Zaenal Abidin; Latianingsih , Nining (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
This community service aims to improve the competence of MSME actors through the implementation of collaborative knowledge creation and pentahelix concepts in digital marketing training. The main problems faced by MSME partners are low digital literacy, limited visual promotion skills, and underdeveloped business collaboration networks. This community service used a descriptive qualitative method through document studies, participatory observation during training activities, and evaluation questionnaires distributed to training participants, including MSME actors from Curug Maju Bersatu and Jakarta Enterpreneur. The results show that 60% of participants strongly agreed that collaborative knowledge creation-based training provided valuable insights and benefits for business development. Additionally, 65% of participants strongly agreed that the pentahelix collaboration was effective for business development, 65% strongly agreed that product photography practice was easy to follow, and 65% agreed that their knowledge and skills in digital marketing and product photography improved after participating in the training. Collaboration among government, academics, communities, and business actors strengthened business networks and enhanced the quality of MSME digital promotions. Therefore, this training received positive responses from participants for being practical and has the potential to become a collaborative-based MSME development model across sectors.